Growth response of Spirulina platensis (Nordst) Geitler, in cabbage extract and antibacterial activities in different culture media (Bangladesh Journal of Scientific and Industrial Research, 2015)
Growth response of Spirulina platensis (Nordst) Geitler in cabbage skin extract media and their antibacterial activities were studied. Five different concentrations e.g. 10 , 8 ,6 , 4 and 2 gm/L of cabbage skin extract media and one BD1 (control) medium were used in this experiment. Highest optical density was observed in 10 gm/L cabbage skin extract medium (0.35) followed by BD1 medium (0.30) after fifteen days of culture. Antibacterial activity of S. platensis was studied. Only freeze dried S. platensis powder extracts showed inhibitory effect against tested bacterial pathogen. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22622 Bangladesh J. Sci. Ind. Res. 49(4), 205-210, 2014